Developmental toxicity of lead in rats after gestational exposure and the protective role of taurine. Issue 8 (27th May 2021) - Aglan, Hoda Samir; Safar, Marwa M; Ain‐Shoka, Afaf Abdel‐Moniem; Kandil, Asmaa Munir; Gebremedhn, Samuel; Salilew‐Wondim, Dessie; Schellander, Karl; Tesfaye, Dawit
Abstract: The present study was conducted to investigate the potential adverse effect of Pb on pregnant Sprague–Dawley rats and their fetuses after maternal exposure, on gestational days (GD) 7–16. The possible protective role of taurine (TA), administered throughout the gestation period (GD 1–20) against Pb toxicity, was also evaluated. Pregnant rats were divided into four groups: Group 1 (control) was given distilled water; Group 2 was exposed to Pb (250 ppm) in drinking water (GD 7–16), whereas Group 3 received TA (50 mg/kg/day) by oral gavage (GD 1–20); Group 4 was exposed to Pb (GD 7–16), whereas pretreated with TA from GD 1 till the end of the gestation period. After termination on GD 20, maternal and embryo‐fetal outcomes were evaluated. Blood samples were collected for hematological and biochemical parameters assessment. The results showed that, Pb induced a significant reduction in the maternal body weight, weight gain, uterine and placental weight, in addition to a high incidence of abortion and fetal resorption. Meanwhile, fetuses demonstrated decreased body weight and length, with a high rate of mortality as well as external and skeletal abnormalities. Additionally, Pb induced severe hematological and biochemical alterations in both dams and fetuses. The toxicity of Pb was further emphasized by placental histopathological examination and hepatic DNA fragmentation. Pretreatment with TA greatly attenuated the impact of Pb on both maternal and fetal parameters. Moreover, TA alleviated the incidence of placental damage and hepatic DNA fragmentation. The results highlight the potential prophylaxis role of TA against maternal and developmental Pb toxicity.